Digital Transformation In Agriculture: Empowering Aceh's Millennial Farmers For National Food Security - Ariansyah, Ricky; Agustina, Agustina; Puspita, Desi; Idris, Iswandi (SEAN Institute, 2024)
The agricultural sector in Indonesia, particularly in Aceh, is experiencing a transformative shift with the rise of digital technologies. This transformation is driven by the active participation of millennial farmers, who are adopting innovative tools such as IoT-based agricultural management systems, mobile applications, and digital platforms. These technological advancements have the potential to revolutionize farming practices, increase efficiency, and ensure the sustainability of food production systems. The article explores the challenges and opportunities in empowering Aceh's millennial farmers through digital tools, enhancing their capacity to contribute to national food security. By leveraging government support and private sector collaborations, millennial farmers are positioning themselves as key players in improving the resilience and sustainability of Indonesia’s food systems. This study highlights the importance of integrating digital literacy in agricultural education and the role of policy interventions in fostering innovation in the agricultural sector